Skupinska dinamika negovalnega tima - Škerbinek, Ladi (Obzornik zdravstvene nege, 1998)
The article defines the most important psychodynamic elements of the group respectively nursing team. The satisfaction of nurses and nursing technicians with their work does not depend solely onthe work itself but to a grat extent also on the team he/she belongs to. The article describes the group and interpersonal relations in it, group dynamics and devlopmental process of the group, respectively team, basic characteristics of team behaviour and leadership.
Keywords: health care; teamsko delo; zdravstvena nega; zdravstvo